Retrofitting of Short Columns by Utilizing Different Galvanized Steel Meshes to Improve Strength Properties - Adnan Khan; Murad Khan; Ghulam Mujtaba; Julius Olayinka Olaniregun; Muhammad Bilal (Journal of ICT, Design, Engineering and Technological Science, 2023)
Retrofitting is the process of adding modern systems to older buildings to make them sustainable. Retrofitting of RC short columns may be defined as an attempt to restore the original strength and stiffness of damaged as well as deteriorated RC short columns. The main purpose of this research project is that many older structures today require strengthening their existing civil engineering infrastructure. The reasons are deterioration by aging or corrosion caused by environmental factors, load increase because of a change of function in the structure, or poor design which does not meet the present more stringent design requirements such as in earthquake areas. In this research, Welded wire mesh was used for Retrofitting to study its confining effect. UN retrofitted & Retrofitted Columns are crushed in UTM. The result observed was positive with a high percentage of increase in strength properties particularly in the case of utilizing square iron mesh which is 14.87% and 34.44% in compressive and tensile strength respectively.